Effect of surya namaskar on anthropometric parameters and serotonin level in apparently healthy subjects - More, Himani Hanumant; Singh, Ajaya Deep; Ghildiyal, Archana (International Journal of Research in Medical Sciences, 2025)
Background: Although surya namaskar was not considered an asana or part of classical yoga, it is now part of modern yoga practise. It consists of twelve postures. Surya namaskar has a profound calming effect and helps to detoxify the deep-seated organs through abundant oxygenation. The purpose of this study was to investigate how surya namaskar affects anthropometric measures, serotonin levels, and anxiety (as measured by the DASS 21 score). Methods: Using inclusion and exclusion criteria, 80 healthy overweight participants (BMI of 23.0-24.9 kg/m2) were selected for the study. They were between 20 and 45 years of age. The subjects practiced surya namaskar 5 days a week for 6 months. Anthropometric characteristics such as height, weight, waist, hip and sagittal abdominal circumference were measured before and surya namaskar sessions. The psychological status of the patients was then assessed using the DASS-21 questionnaire at the time of subject enrolment and after 6 months of surya namaskar. Results: After surya namaskar, there were significant changes in weight (kg), waist circumference (cm), BMI (kg/m2), sagittal abdominal circumference (cm), and WHR were significantly reduced. Hips circumference was mildly increased. Increase in serotonin levels was seen. After surya namaskar, mild depression, severe anxiety and moderate stress were significantly reduced. Conclusions: Surya namaskar has an effect on the physiological, psychological and physical properties of the body. It is recommended to apply surya namaskar in clinical settings to treat psychological stress and obesity.